PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK), DAN DANA BAGI HASIL (DBH) TERHADAP BELANJA MODAL PADA KABUPATEN / KOTA DI JAWA TENGAH (PERIODE 2013-2015) - M. Imad Abdul Majid, 13.05.52.094; Maryono, Maryono (Students' Journal of Accounting and Banking, 2017)
The study examines the effect Local Own Revenue, General Allocation Fund, Special Allocation Fund, and Revenue Sharing Fund on Capital Expenditures. The population in this research is districts or cities government in central java. The population in this study is a districts or cities government in region of central java as 35 districts or cities. The data uses secondary data which has been retrieved of budget realization report in central java 2013 to 2015. This study is a population with a method of data collection is done with the documentary method. Relationship and (or) influence between variable is described by using multiple regression analysis. The result of this study indicate that Revenue, General Allocation Fund and Special Allocation Fund has positive effect on Capital Expenditures. Whereas Revenue Sharing Fund has negative effect on Capital Expenditures.Keywords: Local Own Revenue, General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, and Capital Expenditures